Enhancing the performance of pollution degradation through secondary self-assembled composite supramolecular heterojunction photocatalyst BiOCl/PDI under visible light irradiation. (August 2020) - Ji, Qiuyi; Xu, Zhe; Xiang, Weiming; Wu, Yijie; Cheng, Xinying; Xu, Chenmin; Qi, Chengdu; He, Huan; Hu, Jiapeng; Yang, Shaogui; Li, Shiyin; Zhang, Limin
Abstract: A novel n-n type inorganic/organic heterojunction of flaky-like BiOCl/PDI photocatalyst was constructed by water bath heating method. Meanwhile, a simple method - secondary self-assembly was used to prepare the BiOCl/PDI with a special band structure. The photocatalytic activities were evaluated by degrading aqueous organic pollutants under visible light (λ > 420 nm). The removal rates of 5 mg L −1 phenol (non-ionic type), methyl orange (MO, anionic type), rhodamine B (RhB, cationic type) and 10 mg L −1 RhB by secondary self-assembly BiOCl/PDI (BiOCl/PDI-2) were 8.0%, 3.4%, 27.8% and 78.9% higher than self-assembly BiOCl/PDI (BiOCl/PDI-1) under visible light (λ > 420 nm). The better photocatalytic activity for BiOCl/PDI-2 was attributed to the optimization of energy-band structures, which arose from different exposed surfaces, narrower interplanar spacing and stronger visible light absorption performance. Under acidic condition, BiOCl/PDI-2 showed a good photocatalytic activity, which was not affected by neutral ionic intensity and had good recycling properties. Moreover, the photocatalytic mechanism was explored by free radical capture test and electron paramagnetic resonance (EPR), and contribution of active species was calculated. The main active species of BiOCl/PDI-2 were ·O2 −, 1 O2 and h + . Our work may provide a route to design efficient inorganic/organic heterojunctions for organic pollutants degradation. Graphical abstract: Image 1 Highlights: The flaky-like BiOCl/PDI heterojunction was formed by water bath heating method. The n-n type BiOCl/PDI has superior photocatalytic activity for cationic pollutants. Secondary self-assembly made the π-π stack tighter and enhanced charge transport. Secondary self-assembly can realize energy-band engineering and charge separation.